Structure of the cavalry group of the Crown Standard-Bearer Mikołaj Hieronim Sieniawski, stationed in Moldavia after the battle of Khotyn (Chocim) in 1673 - Hundert, Zbigniew (Balcanica Posnaniensia. Acta et studia, 2023)
On 10 and 11 November 1673 Commonwealth’s armies crushed Ottoman forces at the battle of Khotyn. Victory open new theatre of the operations against High Porte: towards river Danube and on the Polish territories lost in 1672 (Podolia with Kamianets-Podilskyi and Right-bank Ukraine). Polish and Lithuanian troops were very weary after the campaign, what’s more death of King Michał Korybut Wiśniowiecki led to interregnum. Polish command decided to set up the system of border defence, to protect country until the election of new monarch, which should later lead to the new offensive. As such cavalry detachments were spread out in Podolia and Moldavia, while corps under command of Mikołaj Hieronim Sieniawski, Crown Standard-bearer was sent to occupy the latter country. Previous research mentioned that this group had between 6000 and 8000 soldiers. Thanks to document from National Library in Warsaw, we can now identify much more detailed organisation of Sieniawski’s force. He had 48 pancerni banners and two light horse banners, in total 5206 horses. Despite capturing Iași, capitol of Moldavia, Sieniawski’s troops were forced on 17 January 1674 to retreat to Poland, under pressure from the fresh Tatar attack. Despite of the withdrawal from Moldavia, border defence system was still functional and Commonwealth managed fairly quickly to elect new king.